Influence of Streamer's Social Capital on Purchase Intention in Live Streaming E-Commerce - Xu, Ping; Cui, Bang-jun; Lyu, Bei (Frontiers in Psychology, 2022)
The virtual display of products in e-commerce brings new problems of information asymmetry, and the overload of digital information also increases the difficulty of consumers' purchasing decisions. The real-time interaction between the streamer and the consumer during live streaming e-commerce will promote consumers' understanding of the product, reduce information asymmetry, and increase consumers' purchase intention. However, why do people trust the untouchable and unfamiliar streamers from live streaming e-commerce to purchase online? To understand this phenomenon, based on the perspective of information asymmetry theory and parasocial relationship theory, this research identified how social capital affected the purchase intention in live streaming e-commerce. Through a questionnaire survey of live viewers, the purchase intention model constructed by empirical testing was used. The findings showed that the streamer’s professionalism, the reciprocal expectation of the live streaming, and the viewer’s parasocial relationship could effectively increase the viewer’s purchase intention. The occurrence of a streamer’s negative public events could significantly reduce the viewer’s purchase intention. The scale of the live streaming and the streamer's commitment had no significant impact on the viewer’s purchase intention. Trust played an intermediary role between the streamer’s professionalism, parasocial relationship, and the viewer’s purchase intention.